Pengaruh Profitabilitas, Solvabilitas, dan Ukuran Perusahaan terhadap Audit Delay pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Navilla Putri Ardhana; Rispantyo Rispantyo; Aris Eddy Sarwono; Sinta Putriana (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of profitability, solvency, and firm size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The selected period covers the COVID-19 pandemic and the early post-pandemic recovery, during which business operations and audit procedures experienced significant adjustments that may have affected the timeliness of audited financial reporting. This research employed a quantitative approach using secondary data obtained from the annual financial statements of manufacturing companies listed on the IDX. The sample was selected using the purposive sampling method, and the data were analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS). Profitability was measured using Return on Equity (ROE), solvency was measured using Debt to Asset Ratio (DAR), and firm size was measured using the natural logarithm of total assets. The results indicate that profitability and firm size have a negative and significant effect on audit delay, whereas solvency has no significant effect. These findings suggest that companies with higher profitability and larger firm size tend to complete the audit process more promptly